Kratka istorija anestezije - Gazdić, Vera S (Scripta Medica, 2020)
According to the definition of the International Association for the Study of Pain (IASP), pain is defined as: "Unpleasant subjective feeling and emotional experience associated with current or potential tissue damage of a particular localisation", which, as such, poses a challenge for epidemiological research to determine its frequency and prevalence.We have all heard the motto that surgery has experienced its unprecedented development on the wings of anaesthesia. This is most certainly the case, since it is precisely the pain that prevents any invasive procedure on the human body, hence the very elimination of pain has opened up the way for the application and development of surgery. For this reason, the skill and now the science of anaesthesia are epochal civilizational achievements, which is why it is worth remembering the attempts and successes of its application. The very beginning of mankind cannot be imagined without the humans facing some sort of pain. As long ago as about 460 to 370 BC, the renowned Greek physician Hippocrates (in Greek:'Iποκράτης'), who is nowadays considered the founder of modern medicine, stated: "To reduce pain is a divine deed" or, in Latin: Sedare dolorem, opus divinum est!The article presents Morton's discovery of inhalation anesthesia, now as far back as in 1846, its development, introduction of other modes of anaesthesia, local, infiltration and regional, use of neuromuscular blockers and auxiliary procedures, such as endotracheal intubation and fiberoptic bronchoscopy, without which modern anaesthesia is inconceivable today.
Keywords: Bol; Inhalacijska anestzija; Lokalna anestezija; Infiltracijska anestezija; Regionalna anestezija